(untitled) (World Bulletin of Public Health, 2023)
Investigation of anti-EBV IgM va anti-EBV IgG against the Epstein-Barr virus by ELISA and antigen analysis. Material and methods: Materials of the InterMed private clinic located in the Yunusabad district of Tashkent in 2022 were used. For the study, 5 ml of blood from the wrist vein was taken from patients and examined by ELISA (BektoVEB-VCA-IgG-IGM, D2176, D-2184, Vector-Best JSC, Novosibirsk). The results obtained were subjected to statistical processing